COMPARISION OF OUTCOME OF CHEWING GUM VERSUS WITHOUT CHEWING GUM IN POSTOPERATIVE ILEUS AFTER INTESTINAL SURGERY AT TERTIARY CARE HOSPITAL.: JPUMHS;2024:14:04,217-225. http://doi.org/10.46536/jpumhs/2024/14.04.581 - Abdul Rashid Surahio1, Amjad Ali Buhurat2, Faiza Hameed3, Bilal Rasool4, Mohammed Anwer Memon5, Zafar Ali Seenharo6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
OBJECTIVE: To associate the outcome of chewing gum in competition with without chewing gum in Postoperative Ileus patients after intestinal surgery. It causes gasses distention, nausea, vomiting, and even pain. After abdominal surgery. INTRODUCTION: Postoperative Ileus POI is a well-known problem after surgery of abdomen, causing discomfort and delays in bowel movements1. Chewing gum has appeared as a fresh & modest modality for declining postoperative ileus & enhance bowel movemets2. Chewing gum is a cost-effective intervention thought to increase bowel motility by stimulating more secretions and neural signaling to the digestive tract.3. PLACE AND DURATION OF STUDY: study was conducted at department of surgery LUMHS hospital at Hyderabad and jamshoro, for one year starting from the month of January 2023 to the December 2023. MATERIAL AND METHODS: A total number of 208 subjects who achieved the criteria for inclusion & admitted in surgical ward LUMHS, Jamshoro were counted in current research after taking informed permission. The subjects were haphazardly assigned in the direction of either in A group chewing gum & B group without gum chewing were asked to record immediate time of feeling bowl sounds, passing flatus or stool, first time of feeling hunger and time of discharge from hospital which was assessed on post 30 minutes of chewing gum after surgery three times in a day. Entirely the composed statistics were moved into the proforma designed at the completion & used by electronic means for investigation determination.RESULTS: The mean age of A group was 35.53±13.46 & B group was 40.06±12.62 years. In the gender distribution, A group includes 104 individuals, with 61.5% males and 38.5% females. In contrast, B group has 104 individuals, with 66.3% males and 33.7% females. Comparison of outcomes showed mean ± SD for first passage of flatus in 57.32±26.48 in A group and 71.09±28.85 in B group, with highly significant P-value 0.0001, first passage of stool was 86.65±37.56 and 102.28±41.64 with P=0.005, appearance of the first bowel sound had a mean ± SD of 39.67±18.04 and 48.07±17.87, P= 0.001, first onset of the feeling of hunger 66.98±31.32 and 3 93.19±38.84 having P=0.0001 while the length of hospital stay was 8.24±1.91 in A group and 9.04±2.15 in B group , with P= 0.005. CONCLUSION: This study concluded that patients who chewed gum A group with those who did not B group following intestinal surgery, it was observed that chewing gum appeared to accelerate the recovery of bowel function, promote an earlier return of appetite, and result in shorter hospital stays. This suggests that gum chewing may be a beneficial intervention for reducing the impact of Postoperative Ileus in this patient population.